Brief overview of edible insects: exploring consumption and promising sustainable uses in Latin America - Granados-Echegoyen, Carlos; Vásquez-López, Alfonso; Calderón-Cortés, Nancy; Gallego-Ocampo, Heidy Lorena; Gómez-Rodríguez, Carlos Humberto; Rodríguez-Vélez, José Manuel; Sarmiento-Cordero, Mariza Araceli; Salamanca-Canizales, Leidy Julieth; Rodríguez-Vélez, Beatriz; Arroyo-Balán, Fabián; Andrade-Hoyos, Petra (Frontiers in Sustainable Food Systems, 2024)
This review explores the significance of consuming edible insects, as well as their use in the food industry, agro-industry for animal husbandry, agricultural fertilizers and bio-pesticides, and pharmaceuticals. It emphasizes the increasing interest and relevance of this practice. The study starts by investigating the earliest evidence of anthropoentomophagy, which is the consumption of insects by humans, in the region. The review offers an overview of the consumption and utilization of insects in specific regions of the world, emphasizing their significance in various cultures and geographic areas. It also identifies the types of edible insects commonly consumed in Latin American countries, such as Mexico, and explains their preparation and consumption. Furthermore, the review assesses the nutritional value of edible insects, emphasizing their potential as a valuable source of protein, vitamins, and minerals. It also explores the various promising applications of insects, including their role in the food industry, animal husbandry, production of agricultural fertilizers and bioprotectants, and even their potential in the pharmaceutical sector. Finally, the article highlights the significance of entomophagy in Latin America by exploring its historical origins, nutritional benefits, and potential applications in various industries.